2013
DOI: 10.1007/s11103-013-0056-x
|View full text |Cite|
|
Sign up to set email alerts
|

The endoplasmic reticulum stress induced by highly expressed OsrAAT reduces seed size via pre-mature programmed cell death

Abstract: The high accumulation of a recombinant protein in rice endosperm causes endoplasmic reticulum (ER) stress and in turn dramatically affects endogenous storage protein expression, protein body morphology and seed phenotype. To elucidate the molecular mechanisms underlying these changes in transgenic rice seeds, we analyzed the expression profiles of endogenous storage proteins, ER stress-related and programmed cell death (PCD)-related genes in transgenic lines with different levels of Oryza sativa recombinant al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…6B). To further investigate whether the splicing event of OsbZIP50 mRNA occurs under HS, PCR was performed using a specific set of primers (Zhang et al 2013). The results showed that OsbZIP50 splicing was induced after 15 min of 42°C HS but was not affected by LD treatment (Fig.…”
Section: Heat Stress Induces the Unfolded Protein Responsementioning
confidence: 99%
“…6B). To further investigate whether the splicing event of OsbZIP50 mRNA occurs under HS, PCR was performed using a specific set of primers (Zhang et al 2013). The results showed that OsbZIP50 splicing was induced after 15 min of 42°C HS but was not affected by LD treatment (Fig.…”
Section: Heat Stress Induces the Unfolded Protein Responsementioning
confidence: 99%
“…1 I and Additional file 1 : Figure S1C), induced probably by expression of positive regulators of PCD from S2 stage onwards (Additional file 1 : Figure S8B and C). Precocious cellularization and PCD are known to reduce GS in rice [ 25 , 26 ], thus restricting GS in SN, and in turn supporting the postulated “Domino effect”. Essential events occurring during seed development, namely cell cycle, cell expansion, storage accumulation, and PCD, appear to be modulated by temporal regulation of phytohormones in the two genotypes creating differences in GS (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…They can also be transcriptional activators [ 11 ], microtubule-associated proteins [ 22 ], chromatin and histone modifiers [ 23 ], or sucrose transporters [ 24 ]. Any disruption in the timeline of seed development, such as duration of cellularization [ 25 ] and programmed cell death [ 26 ], directly affects GS. Spikelet and cell size of husk also regulate GS [ 8 , 15 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…UPR has also been shown to play a role in regulating seed development. For instance, in rice, overexpression of OsrAAT (Oryza sativa recombinant alpha antitrypsin) in the rice endosperm activates UPR and causes chalkiness in the rice grain [37]. Knockout of OsbZIP60 or overexpression of OsbZIP50, OsBiP1, OsBiP2, and OsBiP3 causes various degrees of chalkiness [38].…”
Section: Introductionmentioning
confidence: 99%